Создание первого в Украине балочного стана - Биллер, В. В.; Попов, А. В. (НТУ "ХПИ", 2009)
Изложена цель, объём и результаты реконструкции рельсобалочного стана на ОАО "Днепровский меткомбинат". Освещены этапы реконструкции. Дано краткое описание технологии производства балок больших размеров с параллельными полками.

The objective, scope and results of the reconstruction of rail and beam mill at JSC "Dniprovskyi Steel" are presented. The reconstruction phases are illuminated. A short description of the production technology of large size beams with parallel flanges are showed.
Keywords: прокатный стан; прокатка; рельсобалочный цех; широкополочная балка; универсальная клеть; rolling mill; rolling; universal beam mill; wide-flange beam; universal stand